2022
DOI: 10.1093/jmcb/mjac051
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of CENP-R by Aurora B regulates kinetochore–microtubule attachment for accurate chromosome segregation

Abstract: Error-free mitosis depends on accurate chromosome attachment to spindle microtubules via a fine structure called the centromere that is epigenetically specified by the enrichment of CENP-A nucleosomes. Centromere maintenance during mitosis requires CENP-A-mediated deposition of constitutive centromere-associated network (CCAN) that establishes the inner kinetochore and connects centromeric chromatin to spindle microtubules during mitosis. Although previously proposed to be an adaptor of retinoic acid receptor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Using chicken DT-40 cells, it was previously shown that CENP-U depletion caused a defect in the recovery of mitosis progression from spindle damage (Hori et al, 2008 ). It is unknown whether this phenotype is due to cohesion defects, or to the impaired function of the CENP-O/P/Q/U/R subunits in modulating kinetochore-microtubule attachment (Amaro et al, 2010 ; Bancroft et al, 2015 ; Hua et al, 2011 ; Pesenti et al, 2018 ; Sedzro et al, 2022 ). If the former is the case, it will be interesting to examine whether the CENP-O, P, Q, or R subunit of the vertebrate CENP-OPQUR complex contains the F/Y-x-F motif that can bind to the Scc1-SA2 sub-complex.…”
Section: Discussionmentioning
confidence: 99%
“…Using chicken DT-40 cells, it was previously shown that CENP-U depletion caused a defect in the recovery of mitosis progression from spindle damage (Hori et al, 2008 ). It is unknown whether this phenotype is due to cohesion defects, or to the impaired function of the CENP-O/P/Q/U/R subunits in modulating kinetochore-microtubule attachment (Amaro et al, 2010 ; Bancroft et al, 2015 ; Hua et al, 2011 ; Pesenti et al, 2018 ; Sedzro et al, 2022 ). If the former is the case, it will be interesting to examine whether the CENP-O, P, Q, or R subunit of the vertebrate CENP-OPQUR complex contains the F/Y-x-F motif that can bind to the Scc1-SA2 sub-complex.…”
Section: Discussionmentioning
confidence: 99%
“…Protein post-transcriptional modification (PTM) influence fundamental properties and cellular biological process, including gene transcription, protein attachment, metabolic reprogramming and so on [21,22]. Several types of PTM with essential functions have been identified on CENPA, including phosphorylation, ubiquitylation, methylation, and acetylation [23][24][25][26].…”
Section: Ivyspring International Publishermentioning
confidence: 99%